(untitled) (International Journal of Environmental Sciences, 2025)
Gas turbines constitute a cornerstone of Iraq’s power generation infrastructure; however, their effectiveness is hampered by the country’s high ambient temperatures, which diminish both efficiency and power output. This analysis explores various air intake cooling strategies aimed at enhancing turbine performance under Iraq’s challenging climate. Techniques such as fogging, evaporative cooling, chilled water systems, and absorption-based cooling are assessed regarding their thermodynamic benefits, cost-effectiveness, water requirements, and compatibility with Iraq’s dry, dust-laden atmosphere. Practical examples from domestic power stations illustrate the pros and cons of deploying these technologies. Evaporative and fogging methods tend to offer modest efficiency boosts at lower costs, whereas chilled and absorption systems provide greater thermal gains but entail higher capital and operational demands. The discussion addresses obstacles such as limited water availability, airborne particulates, elevated maintenance expenses, and system complexity. The study also suggests future advancements including hybrid cooling mechanisms, renewable-powered solutions, smart controls, and innovative materials to elevate performance and reduce ecological impact. Overall, the research highlights the urgency of adopting tailored, sustainable intake cooling systems to meet Iraq’s escalating energy needs and reinforce the stability and resilience of its power sector under extreme weather conditions.